1980
DOI: 10.1159/000121804
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical Mechanisms in Odor-Guided Behavior

Abstract: The role of the thalamocortical ''olfactory'' pathway in odor preferences and sexual behavior was examined in the hamster, a species which depends crucially upon olfaction for mating. Before and after ablation of primary or secondary olfactory structures, male hamsters were tested for threshold, interest, and preference for the odor of an estrus female hamster and other odors. Sexual competency was also observed in daily mating sessions. Disruption of the primary olfactory pathway resulted in an absence of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Lesion studies in rats have shown that MDNT lesions might led to several olfactory functions impairment such as olfactory discrimination (Eichenbaum et al, 1980), odor reversal learning (McBride and Slotnick, 1997) and odor-guided sexual behavior (Sapolsky and Eichenbaum, 1980). …”
Section: Discussionmentioning
confidence: 99%
“…Lesion studies in rats have shown that MDNT lesions might led to several olfactory functions impairment such as olfactory discrimination (Eichenbaum et al, 1980), odor reversal learning (McBride and Slotnick, 1997) and odor-guided sexual behavior (Sapolsky and Eichenbaum, 1980). …”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effect of damage to the MDT in both humans and animal models have provided some useful information about its role in olfaction (Tham et al, 2009 ). The results of these studies have demonstrated that both humans and animal models with MDT damage are not anosmic and do not present deficits in olfactory detection [in rats and hamsters: (Eichenbaum et al, 1980 ; Sapolsky and Eichenbaum, 1980 ); in humans: (Potter and Butters, 1980 ; Sela et al, 2009 )]. Furthermore, humans with Korsakoff’s disease presenting MDT damage are not anosmic but odor detection effects vary between studies, probably depending on the extent of the damage (Jones et al, 1975 ; Potter and Butters, 1980 ; Pol et al, 2002 ).…”
Section: The Still Unclear Role Of the Mdt In Olfactionmentioning
confidence: 99%
“…Relative to perception, Sapolsky and Eichenbaum (1980) have shown that lesions of the MDT alter odor preference in the hamster leading to inappropriate reproductive behaviors. Linked to this distortion of odor preference, studies of patients with damage in the MDT following cerebral hemorrhage, ischemic infarctions, or abscess provide similar evidence.…”
Section: The Role Of the Olfactory Cortex In Odor Perceptionmentioning
confidence: 99%